A combined anterior cruciate ligament/Meniscal injury alters the patellofemoral joint kinematics of anterior cruciate ligament-deficient knees during a single-leg lunge exercise: A cross-sectional study - Huang, Wenhan; Zeng, Xiaolong; Li, Mengyuan; Chen, Haobin; Lai, Huahao; Yan, Yuan; Zhong, Hua; Zhang, Yu (Frontiers in Bioengineering and Biotechnology, 2022)
Anterior cruciate ligament deficiency (ACLD) is often accompanied by concomitant meniscal tears. The aim of the study was to assess the alterations of patellofemoral joint (PFJ) kinematics in ACLD knees with or without meniscal tears during a single-leg lunge. Sixty unilateral ACLD patients were recruited for the study, including 15 isolated ACLD patients, 15 ACLD patients with lateral meniscal injuries, 15 patients with medial meniscal injuries and 15 patients with combined medial/lateral meniscal injuries The PFJ kinematics were determined by a single fluoroscopic image system. PFJ Kinematic alterations were compared between the contralateral ACL-intact (ACLI) and ACLD knees. All ACLD knees, with or without meniscal deficiency, had significantly less patellar flexion than the ACLI knees (~5°-10°; P<0.05). In groups 2, 3, and 4, the injured knees exhibited more patellar lateral tilting by approximately 1° to 2° than the ACLI knees (P<0.05). ACLD groups with medial meniscal deficiencies showed consistent increased lateral patellar translations (2~4 mm) compared to the ACLI group during a single-leg lunge. The results indicate that meniscal injuries alter the PFJ kinematics of the ACLD and the location of the meniscal tear also affects the PFJ kinematics. Considering the varying effects of meniscal injuries on the PFJ kinematics, specific treatments for patients with combined ACL and meniscal injuries should be proposed in some CKC exercise programs, such as single-leg lunge.